Machine learning models for the prediction of levodopa response to tremor in Parkinson’s disease - Li, Fangfei; Lin, Shinuan; Yan, Rui; Cui, Yusha; Ren, Kang; Chen, Zhonglue; Ma, Lingyan; Feng, Tao (Frontiers in Aging Neuroscience, 2026)
ObjectivesTo develop and validate machine learning models to predict levodopa responsiveness of tremor in Parkinson’s disease (PD) patients.MethodsA total of 197 PD tremor patients underwent Levodopa Challenge Tests and were classified as having levodopa-responsive or levodopa-resistant tremor. Clinical and electromyogram (EMG) tremor analysis variables were recorded. The dataset was randomly divided into a training set (80%) and a test set (20%). To distinguish between the two groups, Support vector machine (SVM), random forest (RF), and logistic regression (LR) models were developed using training data. The optimal model was validated on test data. Calibration and decision curve analyses assessed model reliability and clinical utility.ResultsAmong 197 patients, 95 had levodopa-responsive tremor, and 102 had levodopa-resistant tremor. The SVM model showed the best performance, achieving an accuracy of 81.5% in five-fold cross-validation, with a Kappa score of 0.624, sensitivity of 84.3%, specificity of 77.9%, and an area under the curve (AUC) of 0.850. Performance remained consistent on test data, with 82.5% accuracy, 0.653 Kappa, 93.8% sensitivity, 75% specificity, and 0.896 AUC. The best model incorporated 6 predictors: resting tremor score, rigidity/tremor ratio, postural and kinetic tremor score, disease duration, the Movement Disorder Society’s Unified Parkinson’s Disease Rating Scale III (MDS-UPDRS III) /disease duration, and supine diastolic blood pressure (DBP).ConclusionThe SVM model, incorporating six key indicators, holds significant potential for predicting levodopa responsiveness in PD tremor, offering a valuable tool for the precise treatment of tremor in PD patients.